DID A CAPITAL DEEPENING PARADOX AND SWITCHING POINTS OCCUR IN INDONESIA? - Ardyanto Fitrady (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
This paper discusses the empirical results of wage-profit rate schedules between 2000 and 2008 in Indonesia using input-output analysis. Using a mathematical approach, this paper has four main conclusions. First, there is a decrease in both wage share and profit margin in Indonesia. The decrease may be caused by the increase in relative prices of other inputs such as raw materials that generate inefficiency. Second, there is no proof of reverse capital deepening during the observed period and there is an indication that the capital was getting cheaper relative to other inputs during the period. Third, the capital-labor ratio tends to increase over time. Fourth, there is no proof of switching point and reswitching in technology during the period. However, this paper only provides us with an empirical result during the observed period. It is always possible to have a switching point or reswitching in the economy over a longer period.